Network analysis, and human and animal studies disclose the anticystitis glandularis effects of vitamin C. (30th August 2019) - Ge, Bo; Guo, Chao; Liang, Yujia; Liu, Meizhen; Wu, Ka
Abstract: Background: Our present study aimed to unravel the therapeutic biotargets of vitamin C (VC) against cystitis glandularis (CG), and to elucidate the molecular mechanisms for VC treating CG. Methods: Network pharmacology was used to predict therapeutic targets of VC against CG, and to identify molecular mechanisms. In addition, further human and animal studies were designed to validate the bioinformatic findings through biochemical tests, computerized tomography scans, and immunostaining assays. Results: In bioinformatic analyses, pathogenic targets of CG and putative targets of VC were identified, respectively. An interaction network between biological target and functional protein was produced before screening and collecting the key therapeutic targets of VC against CG, biological processes, and signaling pathways. In addition, ingenuity pathway analysis with cloud platform indicated that anti‐CG mechanisms of VC were achieved through modulating a cluster of molecular pathways, such as tumor necrosis factor (TNF) pathway. Meanwhile, 18 core targets of VC against CG were identified, and the most important TNF, interleukin‐6 (IL6), and Jun biotargets were obtained, respectively. In further validation in human study, cellular TNF‐α, IL6, and c‐Jun expressions in patient's CG samples were elevated significantly, accompanied with detectable urinary tract infection. Beneficially, VC‐dosed CG mice resulted in downregulated expressions of endogenous TNF‐α, IL6, and c‐Jun in blood and bladder samples. Conclusion: Collectively, these bioinformatic findings and experimentative data uncover the therapeutic targets and biological mechanisms of VC for treating CG, in which the key biomarkers of TNF‐α, IL6, and c‐Jun may be the potential molecules for treating CG in clinical application.